Sidewall Roughness Measurement and Bearing Performance Simulation of Rock-Socketed Piles Based on Laser Scanning Point Cloud - Junbao Zhang; Yule Hu; Yiteng Wang; Di Zhang (Applied Sciences)
Rock-socketed piles are commonly used in pile foundations for large buildings because of their excellent load-bearing characteristics. The roughness of the pile–rock interface affects the load transfer and the ultimate side resistance of the pile. In this work, a laser radar system is developed to measure the surface roughness of a dry bored pile and the shape of the borehole, and a three-dimensional model of the borehole is reconstructed based on the laser point cloud. The 3D surface model was used to extract the vertical contour lines in different directions and thus calculate the roughness of the pile. A numerical simulation of the real measured 3D model using FLAC3D is presented. A borehole of a real rock-socketed pile was measured and simulated. The results show that, although the working load is carried by both the side and base resistances, the former plays a major role. The slow-varying load-settlement curve indicates that the pile has a superior load–bearing capacity, and the maximum allowable settlement should be considered in the application. The simulations, using the actual piles tested, produced a more realistic load response and were able to predict the load-bearing performance of the piles more accurately. Furthermore, this approach offers a reference for the design of rock-socketed piles.